2020
DOI: 10.3389/fpsyg.2020.01631
|View full text |Cite
|
Sign up to set email alerts
|

Human Choice Predicted by Obtained Reinforcers, Not by Reinforcement Predictors

Abstract: Macphail (1985) proposed that “intelligence” should not vary across vertebrate species when contextual variables are accounted for. Focusing on research involving choice behavior, the propensity for choosing an option that produces stimuli that predict the presence or absence of reinforcement but that also results in less food over time can be examined. This choice preference has been found multiple times in pigeons ( Stagner and Zentall, 2010 ; Zentall and Stagner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…They found strong preference for an optimal alternative that always provided three points over a suboptimal alternative that provided 10 points 20% of the time, and this preference occurred both when the suboptimal alternative was signaled and when it was unsignaled. Stagner et al (2020) also tested adult humans and found results similar to McDevitt et al (2019). In sum, in standard suboptimal choice procedures, adult humans seem less likely than pigeons to choose suboptimal alternatives, but more studies are needed.…”
Section: Suboptimal Concurrent-chains Procedures and Literature Reviewmentioning
confidence: 78%
“…They found strong preference for an optimal alternative that always provided three points over a suboptimal alternative that provided 10 points 20% of the time, and this preference occurred both when the suboptimal alternative was signaled and when it was unsignaled. Stagner et al (2020) also tested adult humans and found results similar to McDevitt et al (2019). In sum, in standard suboptimal choice procedures, adult humans seem less likely than pigeons to choose suboptimal alternatives, but more studies are needed.…”
Section: Suboptimal Concurrent-chains Procedures and Literature Reviewmentioning
confidence: 78%
“…Given that scenarios in which outcomes are learned from experiencerather than descriptionare ubiquitous in everyday settings, examining human choices preferences in paradigms more closely resembling those in the animal literature (i.e., outcomes learned via experience where one option is suboptimal) remains pertinent. Although this question has been addressed in some recent work (Molet et al, 2012;McDevitt et al, 2019;Stagner et al, 2020), studies have yielded inconclusive results and used very small sample sizes (ns < 20) 1 .…”
Section: Figurementioning
confidence: 99%